2022
DOI: 10.1177/21582440211068506
|View full text |Cite
|
Sign up to set email alerts
|

How Does Monetary Policy Uncertainty Influence Firms’ Dynamic Adjustment of Capital Structure

Abstract: This study employs high-dimensional factors model to depict the development of monetary policy uncertainty (MPU) in China over the past decades and develops a logical analytical framework to analyze the effect of MPU on the dynamic adjustment of a firm’s capital structure through bank risk-taking channels. We investigate how MPU affects dynamic adjustment of a firm’s capital structure using a panel data set of China public manufacturers between 2007 and 2018 and find that the higher the MPU, the more detriment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…A sample of industrial companies listed on the Iraq Stock Exchange was selected, as the sample size was (4) companies. The results of several studies (Githaiga, 2021) [18] , (Huang et al, 2021) [21] , (Gunawan et al, 2022, Bogan, 2012 [20,8] , (Denčić-Mihajlov et al, 2015) [11] showed that the financial structure. The dynamic positively affects the financial sustainability.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A sample of industrial companies listed on the Iraq Stock Exchange was selected, as the sample size was (4) companies. The results of several studies (Githaiga, 2021) [18] , (Huang et al, 2021) [21] , (Gunawan et al, 2022, Bogan, 2012 [20,8] , (Denčić-Mihajlov et al, 2015) [11] showed that the financial structure. The dynamic positively affects the financial sustainability.…”
Section: Discussionmentioning
confidence: 98%
“…The results of several studies (Githaiga, 2021) [18] , (Huang et al, 2021) [21] , (Gunawan et al, 2022, Bogan, 2012) [20,8] , (Denčić-Mihajlov et al, 2015) [11] show that the formulation of a financial structure Flexible (dynamic) positively affects the company's returns (return on equity, return on investment).…”
Section: Hypothesis Buildingmentioning
confidence: 99%
“…The existing literature mainly studies the impact of the market-oriented transformation on the economy from the macro and micro levels. At the macro level, the main research focuses on the impact on TFP and believes that the market-oriented transformation is conducive to improving the efficiency of resource allocation [13,14], thereby improving productivity [15]. That is to say, in the case of a higher degree of marketization, capital can move faster from inefficient areas to efficient areas, thereby increasing TFP.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The existing literature mainly discusses the issue of the market-oriented transformation and resource allocation efficiency, and believes that the market-oriented transformation is conducive to improving resource allocation efficiency [13][14][15]. With the improvement of resource allocation efficiency, capital can be transferred from inefficient areas to efficient areas, thereby increasing TFP [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Pa´stor and Veronesi (2013) demonstrate that the predicted risk premium associated with political uncertainty is higher during high EPU. This increase in credit risk impedes firms easy access to external finance and firms generally found more difficulty in getting access to bank loans (Bordo et al, 2016;Gilchrist et al, 2014;Jiang et al, 2022). Additionally, Jiang et al (2022) found that when EPU is heightened, banks tighten loan approval criteria.…”
Section: Economic Policy Uncertainty and Firm Performancementioning
confidence: 99%